Ertugliflozin plus sitagliptin versus either individual agent over 52 weeks in patients with type 2 diabetes mellitus inadequately controlled with metformin: The VERTIS FACTORIAL randomized trial. Issue 5 (25th January 2018) - Pratley, Richard E.; Eldor, Roy; Raji, Annaswamy; Golm, Gregory; Huyck, Susan B.; Qiu, Yanping; Sunga, Sheila; Johnson, Jeremy; Terra, Steven G.; Mancuso, James P.; Engel, Samuel S.; Lauring, Brett
Abstract : Aim: To evaluate the efficacy and safety of ertugliflozin and sitagliptin co‐administration vs the individual agents in patients with type 2 diabetes who are inadequately controlled with metformin. Methods: In this study (Clinicaltrials.gov NCT02099110), patients with glycated haemoglobin (HbA1c) ≥7.5% and ≤11.0% (≥58 and ≤97 mmol/mol) with metformin ≥1500 mg/d (n = 1233) were randomized to ertugliflozin 5 (E5) or 15 (E15) mg/d, sitagliptin 100 mg/d (S100) or to co‐administration of E5/S100 or E15/S100. The primary endpoint was change from baseline in HbA1c at Week 26. Results: At Week 26, least squares mean HbA1c reductions from baseline were greater with E5/S100 (−1.5%) and E15/S100 (−1.5%) than with individual agents (−1.0%, −1.1% and −1.1% for E5, E15 and S100, respectively; P < .001 for all comparisons). HbA1c <7.0% (<53 mmol/mol) was achieved by 26.4%, 31.9%, 32.8%, 52.3% and 49.2% of patients in the E5, E15, S100, E5/S100 and E15/S100 groups, respectively. Fasting plasma glucose reductions were significantly greater with E5/S100 and E15/S100 compared with individual agents. Body weight and systolic blood pressure (SBP) significantly decreased with E5/S100 and E15/S100 vs S100 alone. Glycaemic control, body weight and SBP effects of ertugliflozin were maintained to Week 52. Genital mycotic infections were more common among ertugliflozin‐treated patients compared with those treated with S100. Incidences of symptomatic hypoglycaemia and adverse events related to hypovolaemia or urinary tract infection were similar among groups. Conclusions: In patients with uncontrolled type 2 diabetes while using metformin, co‐administration of ertugliflozin and sitagliptin provided more effective glycaemic control through 52 weeks compared with the individual agents.